2015
DOI: 10.3390/s151026115
|View full text |Cite
|
Sign up to set email alerts
|

Study of Interdigitated Electrode Arrays Using Experiments and Finite Element Models for the Evaluation of Sterilization Processes

Abstract: In this work, a sensor to evaluate sterilization processes with hydrogen peroxide vapor has been characterized. Experimental, analytical and numerical methods were applied to evaluate and study the sensor behavior. The sensor set-up is based on planar interdigitated electrodes. The interdigitated electrode structure consists of 614 electrode fingers spanning over a total sensing area of 20 mm2. Sensor measurements were conducted with and without microbiological spores as well as after an industrial sterilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Another concept to improve the W / L ch ratio of OECTs at limited electrode area are interdigitated electrode (IDE) arrays. IDEs facilitate a significant increase of the channel width and consequently also the W / L ch ratio in comparison to conventional architectures without increasing the device area and its overall capacitance . Hempel et al reported on the fabrication of large area (200 µm × 200 µm) OECTs with interdigitated electrode arrays and their utilization for sensing of clusters of cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another concept to improve the W / L ch ratio of OECTs at limited electrode area are interdigitated electrode (IDE) arrays. IDEs facilitate a significant increase of the channel width and consequently also the W / L ch ratio in comparison to conventional architectures without increasing the device area and its overall capacitance . Hempel et al reported on the fabrication of large area (200 µm × 200 µm) OECTs with interdigitated electrode arrays and their utilization for sensing of clusters of cardiac cells.…”
Section: Introductionmentioning
confidence: 99%
“…The use of capacitive interdigitated electrodes (IDE) has been discussed already in several papers, ranging from gas sensors to liquid sensors [2][3][4][5]. In general, these electrodes are coated with responsive layers that absorb the target molecules.…”
Section: Approachmentioning
confidence: 99%
“…An impedimetric biosensor based on interdigitated electrode (IDE) structures has been developed by the authors in previous work . A test microorganism (spores of Bacillus atrophaeus taken from a spore suspension based on deionized (DI)‐water) has been immobilized on the IDE structure and characterized in respect to the H 2 O 2 sterilization process.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the impedimetric sensor data depends on the electrical properties of the B. atrophaeus spores in air or under low‐pressure conditions. Due to the lack of research on the electrical properties of the spores, analytical methods (e.g., capacitance calculation of IDE structures by applying the complete elliptical integral of the first kind that has been described for the blank structure in our previous article) cannot be applied for verification so far …”
Section: Introductionmentioning
confidence: 99%